Analisis Faktor-Faktor Yang Mempengaruhi Laba Pada Perusahaan Asuransi Umum Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2018-2022 - Mayziah, Silva; Maryati, Ulfi; Ramadhea Jr, Syafira (Politeknik Raflesia Press, 2024)
Insurance is a protection from financial loss in agrees to compensate another party in the event of a certain loss. This study aims to determine the impact of risk based capital, claims expenses, and underwriting results on profit in general insurance companies. The method is a quantitative approach utilizing secondary data obtained from the Indonesia Stock Exchange (IDX) website for the period 2018-2022. The sample involves 7 general insurance companies using purposive sampling. The method analysis used is descriptive statistics using STATA 14.0 software. The result of this study are risk based capital and claims expenses have a positive impact on profits, while underwriting results do not significant affect the profits.